Customer discovery as a tool for moving behavioral interventions into the marketplace: insights from the NCI SPRINT program. Issue 6 (17th July 2019) - Oh, April; Gaysynsky, Anna; Knott, Cheryl L; Nock, Nora L; Erwin, Deborah O; Vinson, Cynthia A
Abstract : The experiences of SPRINT research teams indicate that training behavioral scientists to think about their work through a "customer discovery" lens is potentially beneficial, but also demonstrate the challenges interventionists face when bringing their products to market. Abstract: The National Cancer Institute established a dissemination and implementation accelerator program called Speeding Research-tested INTerventions (SPRINT) in order to expedite the translation of behavioral research into practice. The goal of SPRINT is to introduce researchers to a new method for moving their research into practice in order to increase the real-world impact of their evidence-based interventions. The goal of this article is to present case studies on three teams that have completed the SPRINT program to date. Each case study provides a description of the intervention the team came into the program with, the team's motivation for participating in the SPRINT program, the team's experience in the program, lessons learned from "customer discovery" interviews conducted by the team during the course, and the team's future plans for their intervention. The case studies suggest that by focusing on behavioral researchers, SPRINT addresses an unmet need in the commercialization training space; that the definition of "success" can vary across SPRINT projects; that identifying and engaging "payors" for behavioral interventions is an ongoing challenge; and that there are potential "misalignments" between the research process and market demands. Overall, these examples show that customer discovery is a potentially useful method for making interventions more responsive to the needs of stakeholders, and that researchers can benefit from learning the "language" of business and working with individuals who have business experience before trying to move their research from the lab to the real world.